Odpowiedzi

2010-01-19T12:46:13+01:00
A.
AuB = (-∞,+∞)
AnB = (-3,4)
A' = <4,+∞)
B' = (-∞,-3>
A'uB' = (-∞,-3>u<4,+∞)
A'nB' = Ф

B.
AuB = (-∞,-5)u(5,+∞)
AnB = Ф
A' = <-5,+∞)
B' = (-∞,5>
A'uB' = (-∞,5>u<-5,+∞)
A'nB' = <-5,5>

C.
AuB = (-∞,+∞)
AnB = {3}
A' = (3,+∞)
B' = (-∞,3)
A'uB' = (-∞,3)u(3,+∞)
A'nB' = Ф

Mam nadzieje, że pomogłam ;]
2010-01-19T14:51:41+01:00
A) AuB=(-∞,+∞)
AnB=(-3,4)
A'=<4,+∞)
B'=(-∞,-3>
A'uB'=(-∞,-3>u<4,+∞)
A'nB'=Ф

b)AuB=(-∞,-5) u(5,+∞)
AnB=Ф
A'=<-5,+∞)
B'=(-∞,5>
A'uB'=(-∞,5>u<-5,+∞)
A'nB'=<-5,5>

c)AuB=(-∞,+∞)
AnB={3}
A'=(3,+∞)
B'=(-∞,3)
A'uB'=(-∞,3)u(3,+∞)
A'nB'=Ф

^^